2015
DOI: 10.1177/0091026015604447
|View full text |Cite
|
Sign up to set email alerts
|

What Increases Public Employees’ Turnover Intention?

Abstract: This research examined the extent to which job motivation, social support, public service motivation (PSM), and burnout are related to turnover intention and whether burnout serves as a mediator for these relations. Using data collected from local revenue officers in South Korea, this research found that intrinsic motivation was significantly and negatively related to employees' intention to leave their organization, whereas self-sacrifice (one of the PSM elements) was positively associated with turnover inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 63 publications
2
45
0
6
Order By: Relevance
“…Public Service Motivation (PSM) was identified in previous research (Perry et al 2010;Kim 2015;Vandenabeele 2008) as being linked to a collectivist culture alongside a commitment to implement the public interest. Example items are: 'I am proud to be public service worker'; 'my job is important for the community'; and 'my job allows me to use my skills for the benefit of the public'.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Public Service Motivation (PSM) was identified in previous research (Perry et al 2010;Kim 2015;Vandenabeele 2008) as being linked to a collectivist culture alongside a commitment to implement the public interest. Example items are: 'I am proud to be public service worker'; 'my job is important for the community'; and 'my job allows me to use my skills for the benefit of the public'.…”
Section: Methodsmentioning
confidence: 99%
“…Recently it was defined as ''the belief, values and attitudes that go beyond self-interest and organisational interest, that concern the interest of a larger political entity and that motivate individuals to act accordingly whenever appropriate'' (Vandenabeele 2008). A systematic literature review by Ritz et al (2016) has largely confirmed the positive outcomes of PSM, including staff job satisfaction (Bright 2008), organizational citizenship behaviour (Grant 2007;Kim, 2015;Rayner et al 2012;Taylor 2008) and staff performance (Alonso and Lewis 2001). However, among 400 papers reviewed, the great majority had exclusively researched the white-male workforce, only 15 extant studies had some consideration of ethnic minority workers in the PSM framework (Ritz et al 2016), and this leaves PSM of the ethnic minority group underexplored.…”
Section: Public Service Motivation and Bame Employees In The Ukmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelos que relacionam cognições e comportamentos acumulam evidências no sentido de que a intenção comportamental é um importante antecedente cognitivo do comportamento (Abraham & Sheeran, 2003;Halawi, 2014, Kim, 2015. O construto intenção comportamental foi introduzido no escopo da teoria da ação racional (Ajzen & Fishbein, 1977) e, posteriormente, da teoria do comportamento planejado, como antecessor ao comportamento, e definido como a probabilidade subjetiva de um indivíduo realizar determinado comportamento.…”
Section: Intenção De Sair Da Organizaçãounclassified
“…Pesquisas empíricas internacionais demonstram que a intenção de sair da organização é a variável antecedente cognitiva mais forte da saída voluntária de um profissional (Tett & Meyer, 1993;Joo, Hahn, & Peterson, 2015;Treuren & Frankish, 2014). Por meio de estudos empíricos, contribuições teóricas ou críticas narrativas (Heavey, Holwerda, & Hausknech, 2013), a psicologia organizacional procura investigar como fatores cognitivos, ocupacionais, organizacionais e ambientais influenciam na intenção de profissionais saírem voluntariamente da organização (Kim, 2015).…”
unclassified